2020
DOI: 10.1021/acs.joc.9b03286
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Hydrogen Transfer by Molecular Oxygen and Hydroperoxyl Radicals. Insights into the Mechanism of the Anthraquinone Process

Abstract: Hydrogen atom transfer (HAT) by 3 O 2 and HO 2 • from arenols (ArOH), aryloxyls (ArO • ), their tautomers (ArH), and auxiliary compounds has been investigated by means of CBS-QB3 computations. With 3 O 2 , excellent linear correlations have been found between the activation enthalpy and the overall reaction enthalpy. Different pathways have been discerned for HATs involving OH or CH moieties. The results for ArOH + HO 2• → ArO • + H 2 O 2 neither afford a linear correlation nor agree with the experiment. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 61 publications
3
29
0
Order By: Relevance
“…To arrive at H 2 O 2 from O 2 , two H obviously need to be attached to the latter, and the role of anthrahydroquinone (reduced anthraquinone) consists of providing them by two direct HATs. A number of hydroxyl-containing organic molecules were recently investigated for their HAT ability, 16 but reduced EPI was not among them. In the DFT calculations (including implicit water as solvent) presented above, we studied the interaction between molecular oxygen and EPI-2H as well as between the intermediates resulting after the first HAT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To arrive at H 2 O 2 from O 2 , two H obviously need to be attached to the latter, and the role of anthrahydroquinone (reduced anthraquinone) consists of providing them by two direct HATs. A number of hydroxyl-containing organic molecules were recently investigated for their HAT ability, 16 but reduced EPI was not among them. In the DFT calculations (including implicit water as solvent) presented above, we studied the interaction between molecular oxygen and EPI-2H as well as between the intermediates resulting after the first HAT.…”
Section: Discussionmentioning
confidence: 99%
“… 15 One can legitimately wonder why such a complex procedure was necessary and what is actually the role of anthraquinone. As discussed in a recent and very thorough theoretical study, 16 an enol or a phenol is among rare molecules that can ensure efficient hydrogen atom transfer (HAT) from the hydroxy group to molecular oxygen. Note that the formation of oxygen adduct intermediates has been considered and discarded in both refs ( 14 ) and ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work a crucial step is missing where the hydroperoxyl (OOH • ) radical transitions across the partially dehydrogenated AHQ molecule to perform the second hydrogen abstraction. Given that the overall AQ process is still being determined 30,31 , the goal of this investigation is to calculate the transition of the OOH • across the AHQ molecule in an effort to examine one of many possibilities so that an accurate representation of this process can be determined. It was found that this transition has a deep potential well in the singlet state that probably acts as the rate-determining step as the OOH • transitions across the AHQ molecule.…”
Section: Introductionmentioning
confidence: 99%
“…For example, they are used as stoichiometric reagents (often in combination with strong acids) in a number of (Scholl‐type) aryl‐aryl coupling reactions, and as redox catalysts for example, for the oxidation of amines and alcohols . The anthraquinone process for hydrogen peroxide production is a large‐scale industrial application of quinones . They are also applied in some steps of the synthesis of pharmaceuticals and drugs .…”
Section: Introductionmentioning
confidence: 99%